Edible Coating of Cherry Tomatoes (Solanum lycopersicum) Based on Chitosan Nanoparticles (NPCh) and Mint (Mentha piperita) Essentials Oil with Addition of Aloe Vera Gel - Iftitah, Elvina Dhiaul; Putri, Aufy Nuraini; Soesantyo, Adi Kurnia (Science and Technology Indonesia, 2025)
Cherry tomatoes, as climacteric fruits, continue ripening after harvest, making them susceptible to Xanthomonas campestris bacteria. One method that has been developed to prevent this from happening is applying edible coating with polysaccharides such as chitosan. However, the particles tend to be large and antibacterial activity is not optimal. Therefore, an edible coating was developed using nanochitosan (NPCh) and mint essential oil (EO), enhanced with aloe vera. NPCh was synthesized via ionic gelation with chitosan: STPP ratios of 2:1, 3:1, and 5:1, and mint EO added at 0.2, 0.4, and 0.6 mL. Coatings were applied by dipping, and quality was assessed over 11 days using weight loss, color, Lycopene, Vitamin C parameters, and data result was analyzed with ANOVA (Sig. 0.05). Texture organoleptic tests were evaluated by 10 panelist. Antibacterial activity against Xanthomonas campestris was analyzed in silico. Results showed the smallest NPCh particle size (197 nm) with a 5:1 ratio, and TEM confirmed spherical shapes. Tomatoes without coating (K-) had significantly lower quality compared to coated samples (K+, K1-K6). Samples with EO (K3-K5) preserved physical (weight, color) and nutritional quality (Vitamin C, Lycopene) better, with K5 (0.6 mL EO) showing optimal results. However, there are no significant differences were observed between K5 and K6 (adding aloe vera gel) in maintaining tomato quality. Texture analysis also identified K5 as the most preferred. In silico studies demonstrated strong antibacterial potential for mint EO and aloe vera compounds, with binding affinities (-3.97 to -5.76 kcal/mol) surpassing native ligand and positive control.